2011
DOI: 10.1111/j.1399-0004.2011.01693.x
|View full text |Cite
|
Sign up to set email alerts
|

Phase analysis identifies compound heterozygous deletions of the PARK2 gene in patients with early‐onset Parkinson disease

Abstract: Exon rearrangements and point mutations are common in PARK2, the most important causative gene of autosomal recessive early-onset Parkinson disease (EOPD). However, gene dosage analysis alone cannot conclusively determine the phase of exon rearrangements and the incidence of molecularly confirmed parkin-type EOPD may be underestimated. To fully characterize the mutation spectrum, we performed sequencing and gene dosage analyses of SNCA, PARK2, PINK1, and PARK7 in 114 unrelated EOPD patients with onset age ≤40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 21 publications
1
20
2
Order By: Relevance
“…Gene studies of parkin, PINK-1, DJ-1, SNCA, LRRK2 G2019S, SCA2, and SCA17 mutations were conducted as described elsewhere [27][28][29][30][31]. Parkin mutations were identified by both sequence analysis and gene dosage analysis [multiplex ligation-dependent probe amplification P051/P052 kit (MRC-Holland, Amsterdam, The Netherlands)].…”
Section: Molecular Genetic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Gene studies of parkin, PINK-1, DJ-1, SNCA, LRRK2 G2019S, SCA2, and SCA17 mutations were conducted as described elsewhere [27][28][29][30][31]. Parkin mutations were identified by both sequence analysis and gene dosage analysis [multiplex ligation-dependent probe amplification P051/P052 kit (MRC-Holland, Amsterdam, The Netherlands)].…”
Section: Molecular Genetic Analysismentioning
confidence: 99%
“…Parkin mutations were identified by both sequence analysis and gene dosage analysis [multiplex ligation-dependent probe amplification P051/P052 kit (MRC-Holland, Amsterdam, The Netherlands)]. Detailed methods were previously described [27].…”
Section: Molecular Genetic Analysismentioning
confidence: 99%
“…While compound heterozygous CNVs in PRKN have been previously described in EOPD (Kim et al., 2012), this case is illustrative for several reasons. First, this case demonstrates the utility of CMA in the detection of copy number variation contributing to Parkinson disease and Parkinsonian syndromes.…”
Section: Discussionmentioning
confidence: 98%
“…These data suggest the existence of five additional exons that, however, have never been considered for dosage screening. CNV rearrangements involving PARK2 exons accounts for 50-60% of all pathogenic anomalies, rendering gene-dosage assays essential in Parkin mutational screening [81]. However, the hot-spot nature of this gene makes its quantitative analysis a particular challenge, and several issues need to be pointed out in this regard.…”
Section: Park2mentioning
confidence: 99%
“…Kim et al [81] have showed that phase determination is a prerequisite for PARK2 molecular diagnosis: by phase determination, several patients with apparent contiguous multi-exon deletions were re-diagnosed as compound heterozygotes. Simple gene-dosage assays seem to be not sufficient to determine the phase of rearrangements, and therefore, the true incidence of molecularly confirmed Parkin-type early-onset PD may be underestimated.…”
Section: Park2mentioning
confidence: 99%